CONSUMING INDONESIAN FTV AS MODERN FOLK TALE - Fajar, Dwi Ario (English Language and Literature International Conference (ELLiC) Proceedings, 2021)
FTV (an acronym for Film Television) is part of Indonesian television pop culture. Most Indonesian consumes FTV as daily entertainment. As the pop culture, it has various discourses which is interesting to be discussed. FTV can placed alternatively as modern folktale. It has similiarity from their structure. This article studies the urban culture and superstition which are reflected on FTV. This study uses the approach of naratologi structure by A.J.Greimas to analyze the structure of the story. Descriptive qualitative becomes the method of this study. It reveals thatFTV has similiarity to folk tale. It has the similiar values inside the story.